Allelopathic Potential of Rice Varieties against Spinach (Spinacia oleracea) - Kabir, A. K. M. S.; Karim, S. M. R.; Begum, Mahfuza; Juraimi, Abdul Shukor (2010)
Two laboratory experiments were conducted to investigate the allelopathic effects of rice varieties on spinach (Spinacia aleracea L.). Fifteen rice varieties were included for evaluation. Two methods viz. Sandwich method and Relay seeding method were used to observe the allelopathic effects of rice varieties on seed germination, mean germination time, shoot and root length and dry matter production of spinach as a test crop. Average inhibition in spinach growth was calculated to evaluate the allelopathic potential of the rice varieties. All the selected varieties of rice were more or less detrimental to studied characters of spinach. WITA12 resulted in about 48% average percent inhibition of spinach growth. On the basis of average percent inhibition rice varieties ranked in order of WITA12>Dular>WITA3>BR26>BRRI dhan42>BRRI dhan39>BRRI dhan31>BRRI dhan44>BRRI dhan40>BR19>BRRI dhan43>BRRI dhan46>BRRI dhan47>BRRI dhan45>BRRI dhan28. Both the evaluation methods were positively correlated in determining percent reduction in most of the parameters of spinach due to allelopathic effects of rice.